A structured approach to identifying European critical infrastructures. (2nd June 2010) - Di Mauro, C.; Bouchon, S.; Logtmeijer, C.; Pride, R.D.; Hartung, T.; Nordvik, J.P.
Our increasingly complex and interconnected societies are continuously exposed to a wide range of risks. Infrastructure systems are subject to functional impairments associated with technological failure, natural threats and malicious acts. The adequate functioning of infrastructures is crucially sustaining our societal and economic activities. Therefore, the protection of infrastructures becomes more and more an important issue for policy makers. This paper reports the experience gained during the preparatory studies carried out by the Joint Research Centre (JRC) to support the European Commission and its member states on the definition of criteria for identifying critical infrastructures. The existing methods for identifying critical infrastructures are mainly based on risk analysis techniques. These approaches were found to be insufficient and need to be complemented with socioeconomic evaluations of potential impacts. This paper highlights the contribution of stakeholders and decision makers in the process of definition and identification of critical infrastructures because the concept of criticality is deeply rooted in sociopolitical acceptance.